Sagittal spinal curvatures and pelvic tilt in elite young kayakers - López-Miñarro, P. A.; Muyor, J. M.; Alacid, F. (Medicina dello Sport, 2010)
Aim. The aim of this paper was to describe and compare the sagittal spinal curvatures and pelvic tilt in elite young paddlers in several positions.